2019
DOI: 10.34218/ijm.10.3.2019/001
|View full text |Cite
|
Sign up to set email alerts
|

Using Herzberg Theory to Develop the Employees’ Performance of Rafhan Maize Industry

Abstract: This study determine the impact of Herzberg two-factor theory on employees of Rafhan industry. The current paper applies Herzberg two-factor theory for improving the employees' performance. Seven point Likert scale is used for survey purpose. Descriptive statistics, Reliability test, Pearson correlation, Analysis Of Variance (ANOVA), t test and multiple regression techniques are used for data analysis. Convenience non-probability sampling and random probability sampling are applied in this study. The results h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
2
7
0
1
Order By: Relevance
“…The results of this study are supported byZell & Lesick (2021) , who conducted a meta-analysis of the Big Five Personality Research on performance. Big Five traits have strong relationships with performance and fluctuate across personality and performance dimensions(Zell & Lesick, 2021) .Based on the findings of previous studies, the hypotheses of this study are: H1: There is a relationship between big five personality and job performanceThe relationship between employee motivation and job performanceBased onKhan et al (2018) the motivation possessed by banking industry employees is crucial because motivation positively influences job performance.Providing benefits, recognition, empowerment, and a job environment will increase employee motivation in the banking industry Shaikh et al (2019). also supported this research, which found that motivational factors became a strong predictor in influencing job performance.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The results of this study are supported byZell & Lesick (2021) , who conducted a meta-analysis of the Big Five Personality Research on performance. Big Five traits have strong relationships with performance and fluctuate across personality and performance dimensions(Zell & Lesick, 2021) .Based on the findings of previous studies, the hypotheses of this study are: H1: There is a relationship between big five personality and job performanceThe relationship between employee motivation and job performanceBased onKhan et al (2018) the motivation possessed by banking industry employees is crucial because motivation positively influences job performance.Providing benefits, recognition, empowerment, and a job environment will increase employee motivation in the banking industry Shaikh et al (2019). also supported this research, which found that motivational factors became a strong predictor in influencing job performance.…”
supporting
confidence: 69%
“…The findings of this study are consistent with the theory and prior research. Previous studies indicate that personality significantly influences job performance (Shaikh et al, 2019).…”
Section: The Effect Of Employee Motivation To Job Performancementioning
confidence: 99%
“…Thus, a key consideration in the financing and investment decisions made by organizations is financial constraint (Xiao & Wang, 2020). An index called KZI, based on some key indicators of access to finance such as debts, equity, Tobin's q, dividends, cash flows and cash was developed by (Kaplan & Zingales, 1997), and has been widely used and proven to be an integral measure of financial constraint of firms (Ahmed et al, 2022;Farooq, 2020;Li & Ling, 2021;Akhbar et al, 2021;Shaikh et al, 2021). However, some scholars argued for other measures such as the ACW index, WW index, SA index as well as the text based index to measure financial constraint (Almeida et al, 2004;Whited & Wu, 2006;Hadlock & Pierce, 2010;Hoberg & Maksimovic, 2015).…”
Section: Concept Of Financial Constraintmentioning
confidence: 99%
“…Berdasarkan hasil analisis regresi sederhana, ditemukan hubungan yang positif dan signifikan antara motivasi dan kinerja karyawan. Hasil ini sejalan dengan penelitian sebelumnya dari (Shaikh et al, 2019), yang juga menemukan hubungan antara variable motivasi (intrinsic dan ekstrinsic) dengan kinerja. Yang membedakan adalah target populasi yang diteliti, dimana pada penelitian ini yang menjadi populasi adalah karyawan pabrik tepung jagung di India.…”
Section: Pembahasanunclassified